Effect of School Leadership, Teacher Professionalism, and Community Participation on Primary Education Quality - Ladumpe, Arden Rudyatno; Elpisah Elpisah; Hartini Hartini; Suarlin Suarlin (International Journal of Educational Research, 2026)
This study aims to: (1) analyze the influence of principal leadership on educational quality at SD Negeri Bimor Jaya, North Morowali; (2) analyze the influence of teacher professionalism on educational quality at SD Negeri Bimor Jaya, North Morowali; (3) analyze the influence of community participation on educational quality at SD Negeri Bimor Jaya, North Morowali; and (4) analyze the simultaneous influence of principal leadership, teacher professionalism, and community participation on educational quality at SD Negeri Bimor Jaya, North Morowali. This research employed a quantitative approach using an associative research design and an ex post facto method. The population of the study consisted of all teachers at SD Negeri Bimor Jaya, all of whom were included as research samples through a total sampling technique. Data were collected using Likert-scale questionnaires and documentation. Data analysis was conducted using descriptive and inferential statistical techniques, preceded by classical assumption tests to ensure the suitability of the regression model. The results of the study indicate that: (1) principal leadership has an influence on educational quality; (2) teacher professionalism has an influence on educational quality; (3) community participation has an influence on educational quality; and (4) principal leadership, teacher professionalism, and community participation simultaneously influence educational quality at SD Negeri Bimor Jaya, North Morowali. These findings emphasize that improving educational quality requires effective school leadership, professional teachers, and active support and involvement from the community.